Effectiveness and Efficiency of Using Shared Networks Using Thin Clients to Reduce Office Network Load - Kristiyanto, Yogi; Sugiyono, Sugiyono; Sarah, Siti; Susanto, Yodi; Muzaeni, Amin (International Journal of Informatics, Economics, Management and Science, 2025)
The use of networks in conjunction with thin client systems has become an alternative solution for increasing the efficiency of information technology infrastructure in office environments. Several previous studies have examined the benefits of using thin clients, including cost efficiency, data security, and reduced system administration burden. For example, using thin clients can reduce bandwidth consumption compared to using conventional PCs on a local office network. Another study also stated that thin client systems can extend hardware lifespan and significantly reduce total cost of ownership. These studies emphasize the significant potential of using thin clients in creating more efficient and manageable networks. This study aims to test the effectiveness and efficiency of using a thin client-based shared network in a medium-sized office. The methods used were quantitative studies and field experiments, observing network load (bandwidth usage), server performance, and application response times between conventional PC and thin client. The results showed a 78,35% reduction in network load. In conclusion, this study demonstrates that the use of networks combined with a thin client approach not only reduces network load technically but also has a long-term impact on organizational efficiency, device sustainability, and adaptability to more resource-friendly technological developments.